A Predictive Algorithm for Crosstalk Peaks of SiC MOSFET by Considering the Nonlinearity of Gate-Drain Capacitance - Li, Hong; Jiang, Yanfeng; Qiu, Zhidong; Wang, Yuting; Ding, Yuhang (IEEE transactions on power electronics, 2021)
A predictive algorithm for accurately determining the crosstalk peaks caused by SiC MOSFET s is proposed in this article, which is very important to better design the drive and protect circuits of SiC MOSFET s. Compared to the conventional algorithm of crosstalk peaks, the nonlinearity of gate-drain capacitance ( C gd ) is first considered in the proposed algorithm. In detail, the differential expression of the crosstalk peaks is deduced, in which, the main factors affecting crosstalk peaks are all included. Following, the execution flow of the predictive algorithm is provided according to the differential expression. To verify the accuracy of the proposed algorithm with considering the nonlinearity of C gd , the simulation and experiment platforms are established and verified by using Kelvin packaged SiC MOSFET IMZ120R045M1 (1200 V/52 A). The calculation results of the proposed algorithm are compared with the conventional algorithm without considering the nonlinearity of C gd under different working conditions of SiC MOSFET . Finally, the calculation results, the simulation, and experiment results show that the proposed algorithm is effective and has better accuracy. Therefore, the predictive algorithm proposed in this article provides a theoretical reference to better design the drive and protect circuits of SiC MOSFET s.